Experimental Investigation of Mechanical, Permeability, and Microstructural Properties of PVA-Improved Sand Under Dry-Wet Cycling Conditions - Li, Zhongyao; Zhao, Zhewei; Shi, Haiping; Li, Wenwei; Wang, Baotian; Wang, Peiqing (Frontiers in Physics, 2021)
To improve the stability of sand slopes in Southeast Tibet, the wet–dry cycle test, immersion test, and permeability test were carried out using polyvinyl alcohol (PVA) as the improving material. The improvement effect was evaluated by considering the unconfined compressive strength. The results reveal that the unconfined compressive strength of the improved soil significantly increased with the PVA content, while the degradation of the improved soil by wet–dry cycling and water immersion weakened. However, the permeability of the improved soil slightly decreased compared with that of unmodified soil. Through scanning electron microscopy (SEM), it was found that PVA only forms an elastic network structure in the sand to wind and connect the soil particles, but pores remain in the sand. This indicates that the addition of PVA does not affect the permeability to a great extent, but greatly increases the strength. The findings of this study provide a useful reference for the practical application of PVA.